Bond behavior degradation between FRP and masonry under aggressive environmental conditions. Issue 1 (2nd January 2019) - Ramirez, Rafael; Maljaee, Hamid; Ghiassi, Bahman; Lourenço, Paulo B.; Oliveira, Daniel V.
Abstract: Application of Fibre Reinforced Polymers (FRPs) as external reinforcement for masonry structures has been found to be a promising technique, but the long-term behavior of such systems still needs attention. This study presents an overview of the experimental activities followed by the authors on durability of externally bonded FRP-masonry components subjected to water immersion and accelerated hygrothermal exposure. Both moist and hygrothermal environments were found to be extremely deteriorating in the studied materials and led to significant degradation of mechanical properties and loss in bond strength. The effect of mechanical surface treatment on the bond durability performance was also investigated.